Contribution to the subfamily Ophioninae (Hymenoptera: Ichneumonidae) of Southern Europe with the description of one new genus and 15 new species - Johansson, Niklas (Zootaxa, 2021)
This paper presents the descriptions of four new species of the genus Enicospilus Stephens, 1835 and ten species of Ophion Fabricius, 1798: Enicospilus (Allocamptus) izquierdoae sp. nov., E. borderai sp. nov., E. erebus sp. nov., Ophion albanicus sp. nov., O. anatolicus sp. nov., O. canariensis sp. nov., O. castilloae sp. nov., O. cypriotus sp. nov., O. incarinatus sp. nov., O. trochantellatus sp. nov., O. mediterraneus sp. nov., O. pusillus sp. nov., O. rugipleuris sp. nov. and Ophion ziczac sp. nov. Additionally, a new genus Nyxia gen. nov. and its only known species Nyxia shawi sp. nov. is decribed from Portugal. Enicospilus arcuatus (Brullé, 1846) syn. nov. and Enicospilus hannibalis (Kohl, 1905) syn. nov. are junior synonyms of Enicospilus inflexus (Ratzeburg, 1844). Enicospilus ramidulops Scaramozzino, 1986 syn. nov. is a junior synonym of Enicospilus bimaculator Aubert, 1979. The mainly Afrotropical species Enicospilus antefurcalis (Szépligeti, 1908) is a new record for the Palaearctic realm. A short discussion on the presumed diversity of Western Palaearctic Ophioninae is given.